What Viktor Frankl did for me: a personal appreciation - Denise Hartley (Mental Health and Social Inclusion, 2026)
Purpose This paper aims to examine the influence of Viktor Frankl’s work on the author’s lived experience of childhood trauma, mental illness, addiction and long-term recovery. It explores how Frankl’s central concepts illuminate the psychological, relational and spiritual processes through which individuals reconstruct identity and purpose following profound adversity. The paper positions Frankl’s work as a conceptual bridge between existential theory, lived experience and contemporary recovery-oriented practice. Design/methodology/approach Drawing on an autoethnographic and phenomenological methodology, the paper integrates first-person narrative with existential psychology, developmental trauma and recovery research. Frankl’s writings and biography are used as interpretive frameworks for analysing experiences of fragmentation, despair and re-orientation towards meaning. The approach foregrounds the epistemic value of lived experience and situates the author’s trajectory within broader theoretical and clinical debates concerning addiction, trauma and recovery. Findings The analysis demonstrates that Frankl’s work provides a coherent interpretive structure for understanding addiction not solely as pathology but as a response to profound disconnection, disrupted meaning and the collapse of self-world relations. His emphasis on dignity, agency, responsibility and self-transcendence offered the author a stabilising orientation during periods of existential collapse and ultimately influenced both clinical practice and doctoral research. The findings highlight the centrality of meaning-making, identity reconstruction, relational integration and attitudinal shifts in supporting long-term recovery and psychological integration. Practical implications The paper underscores the relevance of existential and meaning-centred approaches within trauma-informed and recovery-oriented practice. Frankl’s concepts offer clinicians and individuals a framework to reframe suffering, reclaim agency and cultivate purpose, particularly in contexts marked by complex trauma and addiction. The analysis affirms the importance of integrating lived experience into theoretical development and clinical application, suggesting that meaning-making processes constitute a vital pathway towards resilience, coherence and flourishing in recovery. Originality/value This is an autoethnographic account of the role of Frankl in the recovery journey of one woman, as she battled trauma, addiction and mental illness. Frankl became known to her via his published works, which she found not just inspirational but life-saving.